Drug compliance and the elderly: who is publishing, where, and when? - Teixeira Jorge Juarez Vieira; Lefèvre Fernando; Castro Lia Lusitana Cardoso de; Spínola Aracy Witt de Pinho (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
Population aging has occurred in a rather heterogeneous way worldwide. The increasing size of the elder age group highlights various health-related problems for the elderly. One such issue is non-compliance with drug prescriptions, a potential source of serious, even life-threatening problems for the patient. The authors have proposed to identify and rank countries that develop research on drug compliance among the elderly, relevant periodicals, and the frequency articles were published between January 1987 and December 1997. A descriptive study was carried out on the basis of a bibliographical review. Three databases were surveyed: MEDLINE, SOCIOFILE e LILACS. The sample included 440 articles, limited to the behavioral sphere. The number of periodicals recorded was 255, varying from one to ten articles. The number of articles published during the study period varied from 23 in 1987 to 49 in 1992, dropping to 29 in 1997. Frequency of the number of articles/year was erratic up to 1992, leveling off from 1993 on at more than double the baseline figure. The authors emphasize the need for developing multi-focused research worldwide.